Does Schizophrenia Itself Cause Obesity? - Liang, Jiaquan; Cai, Yanshan; Xue, Xiongyan; Li, Xiaoling; Li, Zaifang; Xu, Caixia; Xie, Guojun; Yu, Yang (Frontiers in Psychiatry, 2022)
Background Schizophrenia (SC) is considered the most serious of all mental disorders. Some antipsychotics are associated with weight gain and metabolic abnormalities. Whether SC itself causes obesity remains uncertain. Methods We collected 185 first-episode drug-naive SC and 59 healthy controls (HCs) from the Third People’s Hospital of Foshan, Guangdong, China, and distinguished their course of disease in order to understand the body mass index (BMI) and body fat metabolism of SC. Results We found that excluding the drug factors, the longer the course of SC, the more obvious the increase of BMI and the higher the proportion of obesity. BMI was positively correlated with age, course of disease, fasting blood glucose (FBG), low-density lipoprotein (LDL), triglyceride (TG), and total cholesterol (TC), and negatively correlated with high-density lipoprotein (HDL). The results of regression analysis were further proof that age (B = 0.094, p < 0.001), duration (B = 0.081, p = 0.002), FBG (B = 0.987, p = 0.004), and TG (B = 0.918, p = 0.002) were the risk factors for the increase of BMI. HDL (B = –2.875, p < 0.001) was the protective factor. Conclusion SC itself can increase BMI and easily lead to obesity. We should pay more attention to the monitoring of blood metabolism indicators, so as to reduce the risk of obesity and improve the quality of life of patients.